Resource development conflict: a quantitative approach. Issue 1 (17th July 2017) - Lytle, Murray; Hitch, Michael
Abstract : Purpose: The purpose of this paper is to propose the thesis that how an individual views the world – their worldview – is indicative of their acceptance of resource development. A definition of worldview is given and the significance of worldview to cultural and civilizational development is described. A methodology for testing the hypothesis is described and the results of a survey used to collect data are analyzed. At least for the approximately 300 respondents to the survey, there is a correlation between their responses to a series of worldview questions and their acceptance of resource development. Not surprisingly, the correlation becomes stronger as the homogeneity of the respondent group increases. The results of the survey analysis are then compared to a known resource development conflict in a case study to understand the potential significance of the results in a real-world setting. Design/methodology/approach: A definition of worldview is given and the significance of worldview to cultural and civilizational development is described and evaluated. A methodology for testing the hypothesis is described and the results of a survey used to collect data are analyzed. Findings: At least for the 300 respondents to the survey, there is a correlation between their responses to a series of worldview questions and their acceptance of resource development. The case study indicates that respondents can hold contradictory views depending upon the level of inquiry. Research limitations/implications: The sample size is too small to draw any but the most preliminary of conclusions. However, the correlations are high enough to encourage additional work. Practical implications: The research may point to a relatively simple means of understanding the level of acceptance of resource development among all parties to a development proposal. This will allow proponents to identify issues early enough to address them in the design and negotiation phases of project development. Social implications: Resource developers and residents local to the proposed development are often talking at cross-purposes because the issues are not understood at a deep enough level. Once issues are understood at the deeper level of worldview opportunities for resolution may be identified. Originality/value: As far as the researchers are aware this is the only published methodology for quantifying the acceptance of resource development. As identified by the case study, it is possible for a community to reject resource development for reasons that have little to do with resource development either in the particular or in the general.